The genus Senna Mill. (Leguminosae: Caesalpinioideae) in the Serra Geral of Licínio de Almeida, Bahia, Brazil (Acta Scientiarum. Biological Sciences, 2017)
Senna includes about 300 species with circumtropical distribution, widely represented in the Americas, also occurring in Africa, Australia, Asia and Oceania. The genus is represented in Brazil by 80 species, of which 26 are endemic. The Serra Geral de Licínio de Almeida (SGLA), situated in the central portion of the Cadeia do Espinhaço, state of Bahia, Brazil, presents areas relatively little studied, with great potential for the registration of new information about Brazilian biodiversity. The floristic survey of Senna in the SGLA included analysis of specimens collected from February 2012 to October 2013. The analyses were supplemented with dried collections from the following herbaria: ALCB, BHCB, HUEFS, HUNEB, HRB, MBM and SPF.The genus is represented in the study area by 14 taxa, the most representative in the area were: S. silvestris subsp. bifaria var. bifaria, S. macranthera var. striata and S. macranthera var. nervosa, occurring principally in cerrado environments. The taxonomic treatment includes a key for the identification, descriptions, illustrations, photos, data of the geographical distribution, reproductive phenology and comments about the taxa.